Desenvolvimento de biofilme de poli "l-ácido" lático e nanofibras de celulose bacteriana com incorporação de curcumina para embalagem inteligente de alimentos - Silva, Thiago Alves (2023)
The search for the development of renewable biofilms is an alternative for the development of intelligent packages that reduce the environmental impact of materials derived from petroleum. In this study, we present a method of developing a poly-lactic acid biofilm using bacterial cellulose nanofibers as reinforcement and incorporating curcumin for application in smart food packaging. Bacterial cellulose nanofibers were produced through sonication and lyophilization techniques and created to the biofilm through the solvent casting technique. Curcumin was adsorbed to the biofilm through immersion with ethanol. The effects of incorporating 0.5%, 2.0% and 5.0% of bacterial cellulose nanofibers into the poly lactic acid biofilm were considered. The thermal properties were evaluated using the DSC technique, where there was a reduction in the melting and crystallization temperature and an increase in the glass transition temperature and in the crystallinity of the biofilms according to the increase in the percentage of added nanofibers. The addition of 0.5% and 2.0% as reinforcement increased the material resistance, verified through Young's modulus, by 4.5% and 17.4%, respectively. Using the SEM technique, it was possible to evaluate the size of bacterial cellulose nanofibers and their incorporation into the structure of biofilms. Analyzes of water vapor permeability and oil permeability demonstrated that the material has application for fresh foods, since the addition of nanofibers increased the WVR. The analysis of ammonia detection and food suggestion after incorporation of curcumin demonstrated that the biofilm can be used as an active indicator for foods that release ammonia in their research. Due to the compatibility of bacterial cellulose with poly lactic acid and curcumin, one can design the use of these biofilms for application in smart food packaging.